2014
DOI: 10.1080/03057925.2013.876310
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a secondary school teacher in England and France: contextualising career ‘choice’

Abstract: This article explores the circumstances in which individuals become secondary school teachers in England and France. Using a social constructivist theoretical framework, it specifically considers how national contexts play out in this decision. The findings presented in this paper draw on a corpus of 60 interviews with a sample of teachers based in English and French secondary schools. They show that national frameworks remain relevant to an exploration of teachers' identities and cultures, as French and Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
(29 reference statements)
0
11
0
9
Order By: Relevance
“…From the lens of the tripartite model, a consistent finding from research conducted in the western countries is that people are primarily intrigued by intrinsic and altruistic reasons to join teaching (Kyriacou & Coulthard, 2000;Manuel & Hughes, 2006), while the influence of external factors is far less prominent. That is, people are drawn to teaching largely because they love working with children, love a particular subject, or love teaching in general (Mee, Haverback, & Passe, 2012;Moreau, 2014), or because of the intellectual fulfillment that teaching affords (Butt, MacKenzie, & Manning, 2010). Other altruistic motivations include teaching as a calling (Marshall, 2009;Mee et al, 2012), the opportunity to make a difference to the students and the society (Ganchorre & Tomanek, 2012).…”
Section: Studies On Teaching As a Career Choicementioning
confidence: 99%
“…From the lens of the tripartite model, a consistent finding from research conducted in the western countries is that people are primarily intrigued by intrinsic and altruistic reasons to join teaching (Kyriacou & Coulthard, 2000;Manuel & Hughes, 2006), while the influence of external factors is far less prominent. That is, people are drawn to teaching largely because they love working with children, love a particular subject, or love teaching in general (Mee, Haverback, & Passe, 2012;Moreau, 2014), or because of the intellectual fulfillment that teaching affords (Butt, MacKenzie, & Manning, 2010). Other altruistic motivations include teaching as a calling (Marshall, 2009;Mee et al, 2012), the opportunity to make a difference to the students and the society (Ganchorre & Tomanek, 2012).…”
Section: Studies On Teaching As a Career Choicementioning
confidence: 99%
“…The shift in responsibility from state to the individual, as part of the UK 'cost-saving agenda' which had begun in the 1990s (Kilkey et This paper contributes to studies interested in the complexity emerging from socioeconomic disparities and differing cultural values and understandings (such as Fung 2014; Tan and Chua 2014). In the following sections, I discuss how the comparative case study confirmed research which suggests that the national context is influential to translations of international ideas and has significance for individual agency and supposed 'choice' to transcend contextual influences (Moreau 2014).…”
Section: Considering the Developing/ed Context Of The Cases Studiedmentioning
confidence: 80%
“…Bullough and Hall-Kenyon (2012) point out that a calling or vocation are rather rare concepts in contemporary research, whereas Moreau (2015) notes that the term vocation is still used within media and policy circles. 2 However, there is research evidence that having a sense of calling is common among teachers (Bullough & Hall-Kenyon 2012;Richard son & Watt 2006), and that they find the most satisfaction in working with and caring for the young (Bergmark et al 2018;Bullough & Hall-Kenyon 2012;Kyriacou & Coulthard 2000;Moreau 2015). Hoyle (1980) refers to an orientation to teaching, which he describes as narrow or wide professionalism (alternatively, restricted or extended professionalism).…”
Section: Teacher Motivationmentioning
confidence: 99%
“…In both countries, all students agreed either strongly or moderately with the statement that the relationship with pupils and the interactive nature of the profession are a very strong motivator for a career choice. Understandably, such an attitude is not subject-specific but is common among all student teachers: teachers find most satisfaction in working with and caring for the young (Bergmark et al 2018;Bullough & Hall-Kenyon 2012;Kyriacou & Coulthard 2000;Moreau 2015). The students commented:…”
Section: Pupils Are a Strong Motivator For Teachingmentioning
confidence: 99%